Watching Doctor Who fan reception and evaluation - Booth, Paul 1981-; Jones, Craig Owen (Bloomsbury Academic, 2020)
"Watching Doctor Who explores fandom's changing attitudes towards Doctor Who . Why do fans love an episode one year but deride it a decade later? How do fans' values of Doctor Who change over time? As a show with an over fifty-year history, Doctor Who helps us understand the changing nature of notions of 'value' and 'quality' in popular television. The authors interrogate the way Doctor Who fans and audiences re-interpret the value of particular episodes, Doctors, companions, and eras of Who . With a foreword by Paul Cornell."--
Keywords: Doctor Who (Television program : 1963-1989); Doctor Who (Television program : 2005- ); Doctor Who; Science fiction / bicssc; Fan; Rezeption; Electronic books